Artykuł poglądowySclerotherapy. Part II – complications - Strzelecka-Węklar, Daria; Żmudzińska, Maria; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
This paper is the second in a series of articles concerning sclerotherapy. We present a review of data on complications in the treatment of telangiectasias and reticular veins. The prevalence of complications is not high, but they may occur in various clinical forms. Allergic reactions are mainly related to polidocanol hypersensitivity. Hyperpigmentations, petechiae, ecchymoses, skin necrosis, secondary telangiectasias, vessel thrombosis, deep vein thrombosis or pulmonary embolism, agent arterial injection and vein recanalization are among the most common complications. The knowledge of potential complications may significantly contribute to the improvement of treatment effectiveness and safety.